Morpho-biometric characterization of local chicken population in Niger - Hassan, O.M.; Tiambo, Christian K.; Issa, S.; Hima, K.; Adamou, M.L.I.; Bakasso, Y. (GSC Online Press, 2020)
The present study was initiated to determine the morphobiometric characteristics of local chicken population in Niger. A total of 554 chickens (156 males and 398 females) were sampled in the four (4) agro-ecological zones of the country. A complete description by direct observation, individual weighing and body measurements were performed on the entire sample. The results of the study showed an important diversity of plumage colours in the populations studied. Out of the thirteen (13) plumages stains observed, the most common are red (13.5%), pebbles (12.1%), white (11.9%), golden partridge (11.2%) and the fawn (10.8%). Feather distribution was normal over most of the sample (96.6%). The main tarsal colours observed were white, grey and yellow with respectively 45.1%, 39.0% and 15.3%. The eye colourings were mainly orange (55.1%), yellow (31%) and red (12.1%). A normal ridge was observed on 99.5% of individuals while 80% had a red barbillon. From body measurements, it appeared that only the thoracic perimeter remains decisive in the prediction of individual live weight. The average weight obtained over the whole treated sample was 1141.24g. An ANOVA with sex as a source of variation showed that the roosters had an average weight of 1484.24g much higher than that of hens whose average was 1266.64g. This study only concerned the descriptive part of the local chicken of Niger. Other aspects such as productivity remains to be elucidated to better discover the performance of the local chicken of Niger.